Dogs and the Good Life: A Cross-Sectional Study of the Association Between the Dog–Owner Relationship and Owner Mental Wellbeing - Merkouri, Aikaterini; Graham, Taryn M.; O’Haire, Marguerite Elizabeth; Purewal, Rebecca; Westgarth, Carri (Frontiers in Psychology, 2022)
Dog ownership is believed to benefit owner wellbeing but, contrary to popular belief, there is limited evidence to suggest that simply owning a dog is associated with improved mental health. This mixed-methods study investigates whether dog owners with stronger relationships with their dogs experience better mental health. Participants (n=1693, adult UK dog owners) completed an online survey. Owners’ health was measured using the validated PROMIS questions regarding depression, anxiety, emotional support, and companionship. The dog-owner relationship was measured using the validated MDORS scale, which has three subscales: interaction, emotional closeness, and perceived costs. Univariable and multivariable linear regression analyses were conducted, adjusting for confounding factors. Additionally, positive and negative impacts of dog ownership on mental wellbeing were coded from open questions using thematic analysis. A stronger dog-owner relationship was associated with greater feelings of emotional support and companionship but poorer mental health in terms of anxiety or depression. However, the perceived costs (burden) subscale was consistently associated with better mental health outcomes. Direction of causality cannot be inferred as people with poor mental health may acquire dogs to help relieve symptoms, which qualitative analysis supported. Key themes included positive impacts on owner wellbeing and happiness through providing purpose, companionship and self-acceptance, pleasure and distraction, as well as lessening emotional pain and suffering and reducing risk behaviours. However, negative impacts of a strong relationship include anticipatory grief over loss of the dog, and concerns regarding the burden of responsibility and ability to meet dog’s needs. Perceived ability to adequately meet dog’s needs promoted personal growth and positive relationships with others, whereas perceived inability led to feelings of guilt, or anger/frustration, and reduced autonomy and sense of environmental mastery. Dog ownership contributes to both hedonic and eudaimonic wellbeing in multiple ways, including supporting owners through periods of poor mental health and providing purpose. However, the burden of responsibility and owner and dog characteristics can create challenges, and owners may benefit from support in caring for their dogs and reducing problematic behaviours.